Efficacy and Safety of Larotrectinib in Patients With Tropomyosin Receptor Kinase Fusion–Positive Lung Cancers. (27th January 2022) - Drilon, Alexander; Tan, Daniel S. W.; Lassen, Ulrik N.; Leyvraz, Serge; Liu, Yongmei; Patel, Jyoti D.; Rosen, Lee; Solomon, Benjamin; Norenberg, Ricarda; Dima, Laura; Brega, Nicoletta; Shen, Lin; et al.
Abstract : PURPOSE: Larotrectinib is a highly selective and CNS-active tropomyosin receptor kinase (TRK) inhibitor that has demonstrated efficacy across TRK fusion–positive cancers, regardless of the tumor type. The aim of this study was to assess the efficacy and safety of larotrectinib in patients with TRK fusion–positive lung cancers. MATERIALS AND METHODS: Data from two global, multicenter, registrational clinical trials of patients treated with larotrectinib were analyzed: a phase II adult and young adult basket trial (NCT02576431 ) and a phase I adult trial (NCT02122913 ). The primary end point was objective response rate (ORR). RESULTS: By July 20, 2020, 20 patients with TRK fusion–positive lung cancer had been treated. The ORR by investigator assessment among 15 evaluable patients was 73% (95% CI, 45 to 92); one (7%) patient had a complete response, 10 (67%) had a partial response, three (20%) had stable disease, and one (7%) had progressive disease as best response. The median duration of response, progression-free survival, and overall survival were 33.9 months (95% CI, 5.6 to 33.9), 35.4 months (95% CI, 5.3 to 35.4), and 40.7 months (95% CI, 17.2 to not estimable), respectively. Among patients with baseline CNS metastases, the ORR was 63% (95% CI, 25 to 91). Adverse events were mainly grade 1 or 2. CONCLUSION: Larotrectinib is highly active with rapid and durable responses, extended survival benefit, and a favorable long-term safety profile in patients with advanced lung cancer harboring NTRK gene fusions, including those with CNS metastases. These findings support routine testing for NTRK fusions in patients with lung cancer. Abstract :